PENGARUH MEDIA FLASH CARD TERHADAP PEMAHAMAN MITIGASI BENCANA PADA MATA PELAJARAN IPS KELAS V SEKOLAH DASAR (JS (JURNAL SEKOLAH), 2022)
Abstract : The Effect of Flash Card Media on Understanding Disaster Mitigation School Social ScienceSubject in Class Elementary School. This study aims to determine the effect of flash card media on understanding disaster mitigation in social science subjects for grade v elementary school. The independent variable of this research is flash card media and the dependent variable is understanding of disaster mitigation. This experimental method uses a Quasy Experiment with a research design using the Nonequivalent Control Group Design. The population in this study were students of class V. The sample in this study amounted to 46 people. The sampling technique was done by purposive sampling. Data collection techniques using tests and documentation. The data analysis technique used in this research is the t-test. The results of the calculation of the data analysis data obtained the average value of the control class posttest results of 75.43 and 85.43 for the experimental class posttest. Based on the results of the t-test analysis, the value of t_count = 3.982 is more than t_(table (0.05)) = 2.015 so that Ho is rejected, which means Ha is accepted. Likewise the value of sig. of 0.000 < 0.05. Thus, there is an effect of flash card media on understanding disaster mitigation in social science subjects for grade v elementary school.                                                  Keywords: Flash Card Media, Understanding Disaster Mitigation Abstrak : Pengaruh Media Flash Card Terhadap Pemahaman Mitigasi Bencana Pada Mata Pelajaran Ips Kelas V Sekolah Dasar. Penelitian ini bertujuan untuk mengetahui keefektifan media flashcard dalam memahami mitigasi risiko bencana pada mata pelajaran IPS kelas V SD.. Variabel bebas dari penelitian ini yaitu media flash card dan variabel terikat yaitu pemahaman mitigasi bencana. Metode eksperimen ini menggunakan Quasy Eksperiment dengan desain penelitian menggunakan Nonequivalent Control Group Design.  Populasi dalam penelitian ini adalah siswa kelas V. Sampel dalam penelitian ini berjumlah 46 orang. Teknik pengambilan sampel dilakukan dengan cara purposive sampling. Data dikumpulkan dengan menggunakan tes dan dokumentasi. Teknik analisis data yang digunakan dalam penelitian ini adalah uji-t. Hasil perhitungan data analisis data diperoleh nilai rata-rata hasil posttest kelas kontrol sebesar 75,43 dan 85,43 untuk posttest kelas eksperimen. Berdasarkan hasil analisis uji t menunjukkan nilai  = 3,982 lebih dari  = 2, 015 sehingga  ditolak berarti  diterima. Begitu juga nilai sig. Sebesar 0,000